LATAR SEBAGAI KEKUATAN ANTAGONIS DALAM NOVEL TELEPON KARYA SORI SIREGAR - I Ketut Sudewa (Adabiyyāt: Jurnal Bahasa dan Sastra, 2014)
Setting in a story consists of places, time, and socio-cultural circumstances. It functions to strengthen and to make sense the element of characterization in shaping a story line. Yet, setting can function as an antagonist force to be dealt with by the protagonist character. This interesting phenomenon can be seen in the novel Telepon by Sori Siregar. This research aims at discussing the setting in the novel both as antagonist force and as social criticism. Setting, in other words, is discussed as form, which functions as technique involving story, and as content, which function as social criticism. This research uses the theory structuralism and sociology of literature theory as the framework of analysis. The result shows that the setting of place with its entire problems make the main character, David, acts and behaves against the setting of place. It is a way for the author of the novel criticizes the society, especially people of Jakarta.